Challenges of Blockchain Implementation in Construction - Ahsan Waqar; Lubna A. Alharbi; Faiz Abdullah Alotaibi; Khaled A. Alrasheed; Abdul Mateen Khan; Hamad Almujibah (Journal of Engineering)
The implementation of blockchain techniques in extensive building work undertakings has encountered multiple obstacles. The barriers encompass a variety of areas including technical, functional, economic, social, and standardization concerns. Notwithstanding the growing recognition of the prospective advantages of blockchain technology among the building industry, there exists a paucity of the literature that delves into the obstacles of implementing blockchain technology in extensive building undertakings. The purpose of this study is to check the difficulties attached with the implementation of blockchain technology in extensive building undertakings. This research study uses a mixed-method technique that combines structural equation modelling (SEM) and exploratory factor analysis (EFA) to assess the data gathered from a survey of construction industry experts. The conclusions of this research study recommend that the implementation of blockchain technology in large-scale building projects is significantly impacted by various barriers, including procedural, technical, functional, standardization, social, and economic factors. This research study reveals that the primary obstacles to standardization, technical integration, and functional implementation are the absence of established norms, barriers to assimilating with current systems, and restricted utilization scenarios, respectively. Furthermore, this research study has revealed that the primary, social, and economic hurdles for implementation of blockchain technology in extensive building projects are stakeholders’ reluctance to change, disputes over ownership, and the challenge of demonstrating a definitive return on investment. The study’s implications indicate that the building industry should establish a uniform methodology for implementing blockchain technology that effectively tackles the barriers brought to light in this study. This study’s results provide great views to different stakeholders in the building industry, such as construction managers, investors, and regulators, regarding the difficulties involved in implementing blockchain technology in extensive building projects. The research implications underscore the necessity for a standardized approach to implement blockchain technology in large-scale construction projects. This insight is crucial for construction professionals, investors, and regulators, informing strategic decisions to overcome identified barriers and facilitate the seamless integration of blockchain, thereby enhancing efficiency and transparency in the industry.